The Legal Validity and Evidentiary Challenges of Unwritten Rental Agreements in Boarding Houses - Firnawati; Ma'ruf Akib; Wahyudi Umar (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2025)
The widespread use of unwritten boarding house rental agreements among students generates a distinct form of legal vulnerability, not due to the absence of contractual validity, but as a result of weakened legal certainty and evidentiary fragility. This study employs a normative juridical method with statutory and analytical approaches to examine the legal validity and evidentiary implications of oral rental agreements under Indonesian civil law. The analysis demonstrates that unwritten rental agreements remain legally binding insofar as they satisfy the requirements of Article 1320 of the Indonesian Civil Code. However, the lack of written documentation significantly undermines effective legal protection when disputes arise. Consequently,non-litigation dispute resolution mechanisms, as regulated under Law No. 30 of 1999, emerge as a more functional avenue for resolving disputes, albeit without fully addressing underlying structural imbalances in contractual relations. This study reconceptualizes unwritten boarding house rental agreements as normatively valid yet structurally vulnerable contracts, underscoring the need to strengthen legal certainty in informal contracting practices.